Peran Budaya Organisasi Birokrasi dalam Meningkatkan Kinerja Pelayanan Publik - Setiawati, Budi (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2016)
This article aims to analyze the paradigm shift in the government bureaucracy organization's culture of innovation. In fact, innovation has given a change space and also has a real value in the culture of government organization. This can be proved by the countries in the Asian region continuously make the country become more advanced in their environment. This concept would affect bureaucratic reform in the context of Indonesia. Innovation in the cultural role of bureaucratic organization aims to improve the performance in public services optimally by not changing its identity as professional waiters, which also means changing the mindset of the bureaucratic apparatus more open and adapt to change circumstances within the bureaucracy and as a result of the higher development of science and technology science.